Costly defense in a fluctuating environment-sensitivity of annual Nothobranchius fishes to predator kairomones - Polačik, Matej; Janáč, Michal (Ecology and evolution, 2017)
Antipredator strategies increase the chances of survival of prey species but are subject to trade-offs and always come at a cost, one specific category being the "missed opportunity." Some animals that can modulate the timing of life-cycle events can also desynchronize this timing with the occurrence of a predator. In an unpredictable environment, such a modification may result in a mismatch with prevailing conditions, consequently leading to reproductive failure. In eastern Africa, temporary pools existing only during the rainy season are inhabited by annual fish of the genus Nothobranchius. We examined (i) the capability of multiple Nothobranchius populations and species to cease hatching when exposed to chemical cues from native fish predators and adult conspecifics and (ii) the ability of N. furzeri to modulate their growth rate in the presence of a gape-limited fish predator. As the tested Nothobranchius spp. originate from regions with extreme environmental fluctuations where the cost of a missed opportunity can be serious, we predicted an inability to cease hatching as well as lack of growth acceleration as both the predator's gape limitation and the environment select for the same adaptation. Our results showed no biologically relevant influence of kairomone on hatching and no influence on growth rate. This suggests that, in an unpredictable environment, the costs of a missed opportunity are substantial enough to prevent the evolution of some antipredator defense strategies.
Keywords: tilapia; diapause; embryo; olfactory cue; Clarias